Workshop Penyusunan Perangkat Pembelajaran bagi Guru Matematika SMP/Mts Kabupaten Inhu dalam Menyongsong Kurikulum Merdeka - Sakur Sakur; Nahor Murani Hutapea; Armis Armis; Susda Heleni (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This service aims to provide information to SMP/MTs teachers throughout Indragiri Hulu about the steps for developing innovative MIKiR-based LKPD, provide knowledge to teachers about the strategy for developing the LKPD, train teachers in developing innovative MIKiR-based LKPD, motivate readiness of teachers in welcoming the Independent Curriculum. The results of the community service activities showed that teachers' knowledge of the MIKiR active learning approach in the core components of innovative worksheets was successfully achieved. Participants know that the core component of LKPD is the presentation of information/problems and information reasoning with teacher guidance through questions/orders that are productive, imaginative, open and analytical. Workshop participants can find out what components/terms have changed from the 2013 curriculum to the independent curriculum. It is hoped that the continuation of this workshop activity will allow the teacher to explore more deeply about the development of LKPD as a learning tool. Mathematics teachers are expected to try to implement it in learning in relation to the principles of Independent Learning and freedom to change in the implementation of the Independent Curriculum.